(untitled) (Élisée - Revista de Geografia da UEG, 2024)
This paper goal was to analyze the socioeconomic characteristics of the rural space in the city of São Miguel do Tapuio, Piauí, Brazil. For this, the used data were collected in the websites of the Demographic Census, the Ministry of Development and Social Assistance, Family and Fight against Hunger and the Ministry of Citizenship, besides the indicators of Municipal Agricultural Production (PAM), Municipal Livestock Research (PPM), Plant Extraction and Silviculture Production (PEVS), covering the period between 2000 and 2020, and the 2017 Agricultural Census, through the Brazilian Institute of Geography and Statistics (IBGE). A geoprocessing software was used to construct the location and economic organization thematic maps. The rural space has some deficiencies in the social field, such as in the education and the health, which needs improvement. This space is characterized, primarily, based on traditional agricultural activity, with small producers and the presence of rural development programs. They arose associated with extensive livestock, through the insertion of beekeeping in 2004 and the fish farming in 2013. With this, the sugarcane production remained stable, while the extraction of carnauba powder, charcoal, firewood and wood logs were present in a lesser extent. Keywords: Agriculture; rural space; livestock; socioeconomics.